Embryonic and larval development of river catfish Hemibagrus nemurus (Valenciennes, 1840). - Adebiyi, Fatimat Adenike; Siraj, Siti Shapor; Harmin, Sharr Azni; Christianus, Annie (Academic Journals Inc, 2013)
The aim of this study was to characterize embryonic and larval developmental stages of the river catfish, Hemibagrus nemurus. Fertilized eggs were spherical, adhesive and demersal with a mean egg diameter of 1.5±0.3 mm. Seven embryonic periods were characterized for timing and features: zygote, cleavage, blastula, gastrula, segmentation, pharyngula and hatching. Mean hatch was 23±1 h post fertilization at 27°C. The newly hatched larvae measured 3.0±0.2 mm in total length. Morphogenesis was completed in a day. The yolk sac was completely absorbed in three days. H. nemurus has a short embryonic developmental period in comparison with other catfish species. The information obtained from this study will be useful for egg incubation and larval rearing during the culture of H. nemurus.